Outcomes from a Zoonotic Disease Prioritization workshop using One Health approach in Mozambique, 2018 to 2023 - Inocêncio Chongo; Almiro Tivane; Vanessa Monteiro; Osvaldo Inlamea; Plácida Maholela; Ilda Nhanombe; Saquibibi Ibraimo; John Oludele; Argentina Muianga; Virgílio António; Sádia Ali; Aline Gatambire; et al. (BMC, 2024)
Abstract Introduction Around 75% of (re)emerging infections are of zoonotic origins. The risk of zoonotic transmission in Mozambique is high because approximately 81% of the country's labor force is involved with agriculture, which represents a vulnerability for more frequent human-animal interaction and risk of spillover events. A One Health Zoonotic Disease Prioritization (OHZDP) workshop was conducted in Mozambique to facilitate coordination and collaboration within and across sectors to prevent, detect, and respond to zoonotic disease threats. Based on the success of this integrated workshop, the stakeholders developed actions whose results have a great impact on animal welfare, environment and improving public health. Methods In 2018, representatives from Mozambique's human, animal, and environmental sectors from government, universities, research institutions and partners used US CDC's OHZDP Process to prioritize endemic and emerging zoonotic diseases of greatest national concern and develop recommendations and key interventions needed to advance One Health in Mozambique. After the OHZDP workshop, the Mozambique One Health Secretariat used a theory of change methodology to identify activities for implementation from the recommendations of the OHZDP workshop. Since the OHZDP workshop, the Secretariat has monitored progress of activities annually. Results Mozambique's priority zoonotic diseases are rabies, zoonotic tuberculosis, salmonellosis, zoonotic avian influenza, trypanosomiasis, brucellosis, and Crimean-Congo hemorrhagic fever. One Health recommendations and interventions to address the priority zoonotic diseases focused on One Health collaboration, communication, and coordination; laboratory; surveillance; preparedness and response; prevention; workforce development; and research. After the OHZDP workshop, Mozambique established One Health coordination mechanisms, developed training courses for surveillance, laboratory diagnosis, outbreak investigation, and preparedness and response for the priority zoonotic diseases, conducted joint research, and developed plans. Conclusion Prioritization of zoonotic diseases is critical as it facilitated the key One Health players in Mozambique to optimize resources, gain a greater understanding of zoonotic diseases, and implement policies and activities that promote multisectoral, interdisciplinary, and transdisciplinary collaboration across human, animal, and environmental sectors to prevent, detect, and respond to public health threats. The success of these activities implemented by the local Government and One Health partners were built from the implementation and momentum from the Mozambique's OHZDP workshop.